Hysteria: A South Asian History of Global Medicine. Issue 1 (2nd January 2022) - Pinto, Sarah
Abstract: Ways of mapping mental illness in the world involve stories about history, time and qualities of knowledge. This paper explores the history of hysteria as a South Asian story. With a South Asia-centred history of the contemporary critical concept of cultural translation, this paper observes not only hysteria's long South Asian history, but the colonial emergence of a defining narrative—the equation of hysteria to spirit possession, a naturalised conceptual arrangement that superimposed upon a long history of medical encounters racialised ideas about epistemological difference.